IMPLEMENTATION OF MOTIVATIONAL INTERVIEWING TO INCREASE SELF-ESTEEM ON VICTIMS OF CYBER-BULLYING - Agit Purwo Hartanto (Universitas Pendidikan Indonesia, 2022)
Self esteem is human basic need to fulfill self actualization. Similarly on cyber bullying victim, he/she needs treatment motivational interviewing to support in increasing self-esteem. This research aims to test the effectiveness of motivational interviewing to increase self-esteem on cyber bullying victim. The research method uses pre-test and multiple post-test with control group design engaging 3 experimenter and 12 cyber bullying victim as research subject with subject taking through purposive sampling. Data analysis uses one way mixed ancova repeated measures. The result of this research generally shows that the application of motivational interviewing is effective to improve self-esteem on cyber bullying victim (F (1,9) = 8, 604, p 0,05). Specifically, the effect which can be seen from modification when square root measurement, on experimental group, self-esteem is getting higher while control group is not changing at all. Furthermore, changing also can be seen on the interaction result from intervention, appearing on self esteem’s enhancement, experimental group’s self esteem is higher than control group’s self esteem. (F(3,27) = 10,090, p = 0,05). Therefore, the data above emphasize that individual counseling with motivational approach is relevance to be implemented to increase self-esteem on cyber bullying victim students